Letter from Georg Bredig to Max Bredig, March 18, 1938 - Bredig, Georg (1938)
Georg Bredig (1868-1944) tells his son, Max Bredig (1902-1977), that his personal documents have been returned to him by Third Reich authorities.
Keywords: Bredig, Georg, 1868-1944; Third Reich; Antisemitism; German Jews